2019
DOI: 10.1038/s41386-019-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

Context and topography determine the role of basolateral amygdala metabotropic glutamate receptor 5 in appetitive Pavlovian responding

Abstract: Preclinical data have shown that the excitatory metabotropic Gαq-coupled glutamate receptor, mGluR5, has a role in substance abuse and relapse. However, little is known about the contribution of mGluR5 to the expression of conditioned responding elicited by appetitive Pavlovian cues. We investigated this question in rats that were trained to associate a discrete, auditory conditioned stimulus (CS) with a fructose-glucose solution (5.5% fructose/4.5% glucose; 'sugar'). In subsequent tests for the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In both experiments, CS+ port entries in extinction were significantly higher in context A (the conditioning context) than in context B, and this effect occurred during the initial and second extinction phases. These results replicate prior operant conditioning research (Wing and Shoaib, 2008;Todd, 2013) and concur with our published data using a different Pavlovian conditioning procedure that equated exposure to contexts A and B before test (Remedios et al, 2014;Sparks et al, 2014;Millan et al, 2015;Sciascia et al, 2015;Valyear et al, 2018;Khoo et al, 2019).…”
Section: Extinction Comparisonssupporting
confidence: 90%
See 1 more Smart Citation
“…In both experiments, CS+ port entries in extinction were significantly higher in context A (the conditioning context) than in context B, and this effect occurred during the initial and second extinction phases. These results replicate prior operant conditioning research (Wing and Shoaib, 2008;Todd, 2013) and concur with our published data using a different Pavlovian conditioning procedure that equated exposure to contexts A and B before test (Remedios et al, 2014;Sparks et al, 2014;Millan et al, 2015;Sciascia et al, 2015;Valyear et al, 2018;Khoo et al, 2019).…”
Section: Extinction Comparisonssupporting
confidence: 90%
“…Our primary variable of interest for assessing renewal was a difference score ( CS port entries), which was calculated by subtracting pre-CS port entries from port entries made during the corresponding CS. This variable accounted for individual differences in port entry behavior across rats and has been used previously in appetitive Pavlovian conditioning experiments (Campese and Delamater, 2013;Sciascia et al, 2014;Panayi and Killcross, 2018;Khoo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Male rats were trained to discriminate between a context in which a discrete auditory CS was paired with alcohol delivery and a second different context in which a different auditory stimulus was presented without alcohol delivery. We found that responding to a discrete alcohol-predictive CS was amplified in the alcohol-associated context, compared to the context in which alcohol was never consumed (Khoo et al, 2019a(Khoo et al, , 2019bMillan et al, 2015;Remedios et al, 2014;Sciascia et al, 2015;Valyear et al, 2020). This result indicates that conditioned responding to an alcohol-predictive CS is context-dependent in male rats, but the context-dependency of conditioned responding to an alcohol-predictive CS has not been assessed in females.…”
mentioning
confidence: 65%
“…Next, CS-elicited port-entries were extinguished in both contexts, and then we examined the impact of context in an alcohol-primed induced reinstatement test. Based on prior results (Khoo et al, 2019a(Khoo et al, , 2019bMillan et al, 2015;Remedios et al, 2014;Sciascia et al, 2015;Valyear et al, 2020), we predicted that males would show invigoration of CS-elicited port-entries in the alcohol-associated context compared to the neutral context, during the test and alcohol-primed reinstatement test. Based on growing evidence described above that behaviour in females is not context-dependent, we predicted that responding would not differ between the alcohol-associated context and the neutral context in female rats.…”
mentioning
confidence: 90%
“…In their recent Neuropsychopharmacology article, Khoo and colleagues [6] reported that mGluR5 signaling exerts distinct effects on context discrimination and cue-elicited behavior, depending on the brain site of action. The authors examined the impact of a negative allosteric modulator of mGluR5, 3-((2methyl-4-thiazolyl)ethynyl)pyridine (MTEP), on cue-elicited behavior after Pavlovian conditioning with an auditory cue that predicted delivery of a fructose-glucose solution.…”
mentioning
confidence: 99%